A tale of two cultural life scripts: do young second-generation Turkish immigrants versus young Danes in Denmark perceive life through different cultural lenses?. Issue 6 (3rd July 2021) - Özbek, Müge; Bohn, Annette; Berntsen, Dorthe
ABSTRACT: Cultural life scripts refer to the shared expectations as to the order and timing of life events in a prototypical life course within a given culture or subculture. Immigration is a significant transition that often implies a change in cultural context, which may change people's views about a normative life. However, research on cultural life scripts in the context of immigration has been limited. We addressed this gap by examining the cultural life scripts of 33 young second-generation Turkish immigrants and 33 young Danes in Denmark, pairwise-matched on age, gender, and education, along with their subjective well-being and acculturation level. Both groups reported mostly positive life script events expected to occur in early adulthood and their individual life scripts generally had a positive outlook. In contrast to earlier studies, we found no evidence of lower subjective well-being or greater normativity of the cultural life script in the immigrant group. Moreover, the acculturation level of the Turkish group correlated positively with their subjective well-being, suggesting that adapting at least to some degree to the daily life of the host country is associated with well-being of second-generation immigrants.